Environmental and dietary influences on highly unsaturated fatty acid biosynthesis and expression of fatty acyl desaturase and elongase genes in liver of Atlantic salmon (Salmo salar) - Zheng, Xiaozhong; Torstensen, Bente E; Tocher, Douglas R; Dick, James R; Henderson, R James; Bell, J Gordon (Biochimica et Biophysica Acta (BBA) - Molecular and Cell Biology of Lipids, 2005)
Highly unsaturated fatty acid (HUFA) synthesis in Atlantic salmon (Salmo salar) was known to be influenced by both nutritional and environmental factors. Here we aimed to test the hypothesis that both these effectors involved similar molecular mechanisms. Thus, HUFA biosynthetic activity and the expression of fatty acyl desaturase and elongase genes were determined at various points during an entire two year production cycle in salmon fed diets containing either 100% fish oil or diets in which a high proportion (75% and 100%) of fish oil was replaced by C18 polyunsaturated fatty acid-rich vegetable oil. The results showed that HUFA biosynthesis in Atlantic salmon varied during the growth cycle with peak activity around seawater transfer and subsequent low activities in seawater. Consistent with this, gene expression of Δ6 desaturase, the rate-limiting step in the HUFA biosynthetic pathway, was highest around the point of seawater transfer and lowest during the seawater phase. In addition, the expression of both Δ6 and Δ5 desaturase genes was generally higher in fish fed the vegetable oil-substituted diets compared to fish fed fish oil, particularly in the seawater phase. Again, generally consistent with this, the activity of the HUFA biosynthetic pathway was invariably higher in fish fed diets in which fish oil was substituted by vegetable oil compared to fish fed only fish oil. In conclusion, these studies showed that both nutritional and environmental modulation of HUFA biosynthesis in Atlantic salmon involved regulation of fatty acid desaturase gene expression.